PENGARUH KOMPETENSI DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT. PIONEERINDO GOURMET INTERNASIONAL, TBK. MEDAN (BERGERAK DI BIDANG CFC) - Winda Peronika Siregar; Sartika Sriyanti Simanjuntak; Nurleny Tarigan (JURNAL MANAJEMEN, 2019)
Global competition has been happening this make whole of world preparing qualified product, technology, with human resources to compete and to conquer another countries. Organizations in Indonesia must raise the best strategy in the sphere of organization management. One of the functional focuses of concern by manager is human resources management. One of important assignment the HRM manager that is how to keep and maintain employee performance as organization needs. This research aim to know effect of competence and work stress towards employee performance. Research method used was survey with 83 respondents. Result of this research shows that competence and work stress simultaneously and partialy has positive and significant effect to employee performance.